How Accurate Is the Dating of Scheduled 39-Week Deliveries? - Guseh, Stephanie H.; Little, Sarah E.; Zera, Chloe A.; Robinson, Julian N. (American Journal of Perinatology, 2016)
Objective We assessed the impact of a policy preventing scheduled repeat cesarean deliveries at less than 39 weeks, accounting for potential inaccuracies in pregnancy dating.Study Design We analyzed a cohort of repeat cesarean deliveries before and after the policy change and used chi-square testing to compare the proportion of deliveries at less than 39 weeks. We assessed whether the reduction in early-term deliveries was different if the gestational age was based on the documented estimated date of delivery (EDD) as compared with best obstetric dating.Results Our cohort consisted of 213 women; 112 before the policy change and 101 after. Using the EDD assigned at delivery, there was a 12.1% absolute decrease in scheduled deliveries at less than 39 weeks (25.0–12.9%; p = 0.025). However, using the EDD by best obstetric dating, there was no significant change (32.1–25.7%; p = 0.305). Of the 85 discrepant EDDs, providers were more likely to assign an earlier EDD (63.5%; p = 0.013).Conclusion Our institution's policy change led to a 12.1% absolute reduction in documented, scheduled early-term deliveries, however only a 6.4% absolute decline using best obstetric dating. Policy initiatives to reduce early-term deliveries should consider the source and accuracy of the assigned pregnancy dating.
Keywords: scheduled repeat cesarean; early-term delivery; obstetric dating; delivery policy